L1 Grammar Instruction in Primary School - Cardoso, Adriana (2019)
In Portugal, the traditional practices of L1 grammar instruction essentially involve declarative knowledge, which the student integrates in a way that is dissociated from the social uses of the language. These practices are based on the identification of categories and memorization of labels or definitions and involve 159 activities such as questionnaires on texts and training exercises (Cardoso, Leite, Pereira & Silva 2018; Ferreira 2012, 2014). Some recent studies have shown that there is an alternative way of grammar instruction. New approaches abound both nationally and internationally, namely: grammar instruction in context (Weaver, 2018); grammar didactic sequences (Camps & Zayas 2006; Pereira 2010); new grammar (Nadeau & Fisher, 2006); grammar laboratories (Duarte 2008; Silvano & Rodrigues, 2010; Costa et al. 2011; Silvano & Rodrigues 2010); observation and manipulation of data (Tisset 2008); and language awareness (Denham & Lobeck 2010). In this symposium we present some didactic experiments implemented in primary school (ages 6 to 10) which fall under this innovative line of grammar instruction (Santos, Cardoso & Pereira 2014; Pereira, Santos, Pinto, Silva & Cardoso 2016; Gonçalves, in prep.; Soares, in prep.). These studies involve the construction and implementation of didactic pathways based on seven guiding principles: (i) contextualization of grammar activities; (ii) use of grammatical terminology as a tool and not as an end in itself; (iii) adequacy of activities to the stages of students’ language development; (iv) promoting the discovery and exploration of language; (v) spiral progression of grammatical contents; (vi) promotion of metalinguistic activity; (vii) mobilization of language awareness and (meta)linguistic knowledge in the production of oral and written texts (Sim-Sim, 1998; Costa, Cabral, Santiago & Viegas, 2011; Camps & Milian 2000; Santos, Cardoso & Pereira, 2014; Pereira, Santos, Pinto, Silva & Cardoso, 2016). With the dissemination of these studies, we intend to make available resources that can be used in the classroom and encourage the development of more research in this field.